2013
DOI: 10.1155/2013/839456
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Trial of a Novel Nomogram to Achieve Updated Vancomycin Trough Concentrations

Abstract: Purpose. To determine if the use of a novel vancomycin nomogram predicts dosing regimens that achieve target trough concentrations equal to or more accurate than dosing regimens calculated using traditional pharmacokinetic calculations, evaluate the incidence of subtherapeutic and supratherapeutic troughs, and assess pharmacist's impressions of the nomogram. Methods. Prospective, open-label study in 473 patients who had a new order for vancomycin and were >18 years of age and ≤120 kg. Patients were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 10 publications
1
28
0
1
Order By: Relevance
“…Autoriai aiškina, kad skiriant vankomiciną injekcijomis ir sekant jo koncentraciją, reikalinga didesnė vaisto dozė, norint pasiekti terapinę koncentraciją plazmoje, nei taikant nepertraukiamą infuzinę terapiją [22]. Nors ir atlikta nemažai tyrimų, siekiant nustatyti, kaip tinkamai dozuoti vankomiciną, vieningų rekomendacijų nėra iki šiol [8,23] …”
Section: Diskusijaunclassified
“…Autoriai aiškina, kad skiriant vankomiciną injekcijomis ir sekant jo koncentraciją, reikalinga didesnė vaisto dozė, norint pasiekti terapinę koncentraciją plazmoje, nei taikant nepertraukiamą infuzinę terapiją [22]. Nors ir atlikta nemažai tyrimų, siekiant nustatyti, kaip tinkamai dozuoti vankomiciną, vieningų rekomendacijų nėra iki šiol [8,23] …”
Section: Diskusijaunclassified
“…Trough Levels within a Therapeutic Range 714 mg/L to avoid development of resistance, and ideally between 15 mg/L and 20 mg/L for complicated infections such as osteomyelitis, endocarditis, meningitis, bacteremia, and hospital-acquired pneumonia caused by S. aureus to improve penetration, increase probability of obtaining optimal target serum concentrations, decrease the incidence of nephrotoxicity, and improve clinical outcomes [8,9] 1.2g q12h 1g q8h 1g q8h 1.2g q8h 1.2g q8h 1g q6h 100 1.2g q24h 1.2g q18h 1g q12h 1g q12h 1.2g q12h 1g q8h 1g q8h 1.2g q8h 1g q6h 1g q6h 105 1g q18h…”
Section: Evaluation Of the Effectiveness Of A Vancomycin Nomogram At mentioning
confidence: 99%
“…More recently, several studies have discerned worse clinical outcomes for patients infected by MRSA isolates with a vancomycin MIC ≥ 1 mg/L [5][6][7][8][9]. The pharmacokinetic parameter that best predicts the efficacy of vancomycin is the area under the curve (AUC) to MIC ratio (AUC:MIC) [6,8,9]. Specifically, studies have shown that an AUC:MIC ≥ 400 is associated with clinical success of vancomycin therapy [6,8,9].…”
mentioning
confidence: 99%
See 2 more Smart Citations